Combined MRI-TRUS fusion targeted and systematic biopsy versus systematic biopsy alone for the detection of prostate cancer: protocol for a prospective single-centre trial - Bin Yang; Kun Zhu; Qin Wei; Xudong Yao; Guang Xu; Yanyan He; Wujianhong Liu; Aimaitiaji Kadier; Danjing Shen; Shengrong Dong; Binghui Zhao; Shiyu Mao; et al. (BMJ Open)
Introduction The classic way of diagnosing prostate cancer (PCa) is by conducting the 12-core systematic biopsy (SB). However, it has a low detection rate for clinically significant PCa (csPCa) and can lead to the detection of clinically insignificant PCa (cisPCa). Although MRI-transrectal ultrasound (MRI-TRUS) fusion targeted biopsy (TB) can effectively improve the detection rate of csPCa, it may still miss some cases. Therefore, we propose using a combination of TB and SB methods to enhance the detection rate of csPCa while minimising the detection rate of cisPCa.Methods and analysis This study is a prospective, single-centre investigation that aims to assess and compare the detection rate of csPCa using MRI-TRUS fusion TB combined with SB versus TRUS 12-core SB alone. Biopsy-naïve men with suspected PCa will be subjected to multiparametric MRI. Patients with Prostate Imaging Reporting and Data System (V.2.1) score ≥3 will be enrolled in the TB-SB combination group. The sample size is established as 660 participants, considering a 10% drop-out rate. The primary outcome is the detection rate of csPCa in men without prior biopsy using MRI-TRUS fusion TB combined with the standard TRUS-guided 12-core SB method. CsPCa will be defined as International Society of Urological Pathology Grade ≥2.Ethics and dissemination This study has been approved by the Ethics Committee at the Shanghai Tenth People’s Hospital, an affiliated hospital of Tongji University School of Medicine. The research results will be published in a peer-reviewed international journal.Trial registration number ChiCTR2000036089.